Secretion of DNases by Marine Bacteria: A Culture Based and Bioinformatics Approach - Al-Wahaibi, Aisha S. M.; Lapinska, Emilia; Rajarajan, Nithyalakshmy; Dobretsov, Sergey; Upstill-Goddard, Robert; Burgess, J. Grant (Frontiers in Microbiology, 2019)
The vast majority of bacteria present in the natural environment are present in the form of aggregates and/or biofilms. Microbial aggregates are ubiquitous in the marine environment and are inhabited by diverse microbial communities which often express intense extracellular enzymatic activities. However, the secretion of an important group of enzymes, DNases, by bacteria from marine aggregates has not been studied, despite the importance of these aggregates in biogeochemical cycling of nutrients in the oceans. In this work, we therefore, employed both culture-based and bioinformatics approaches to understand the diversity of bacterial DNases in marine bacterioplankton. We found that 34% of 345 strains of attached and non attached marine bacteria showed extracellular DNase activity. Most of these isolates belong to Proteobacteria (53%) and Firmicutes (34%). Secretion of DNases by bacteria isolated from marine gel particles is reported here for the first time. Then, to further understand the wider diversity of the potential to produce DNases, sequences were compared using 2316 whole genome and 42 metagenome datasets. Thirty-nine different taxonomic groups corresponding to ten bacterial phyla were found to encode genes responsible for DNase secretion. This study highlights the unexpected and widespread presence of DNase secretion in bacteria in general and in marine gel particles more specifically. This has important implications for understanding the dynamics and fate of marine microbial aggregates in the oceans.